Chicago on the nile : a century of work by the epigraphic survey of the university of chicago - Teeter, Emily, (ISAC Museum Publications ;, 2024)
"Chicago on the Nile relates the colorful story of the University of Chicago's Epigraphic Survey expedition to Egypt, from its conception in 1924 by the first American Egyptologist, James Henry Breasted, through its development over the course of a century to become the major scientific and social presence it is today-not just in Egypt but throughout the world. Initially envisioned as a small group of scientists devoted to documenting the ancient historical inscriptions and reliefs on the walls of the temple of Medinet Habu in Luxor, the Epigraphic Survey's work grew to encompass many of the most important sites in Egypt, including Karnak, Luxor Temple, the tomb of Kheruef, Saqqara, Abydos, and the Beit el-Wali temple in Nubia. The story places this work within the larger contexts of Egyptian and international politics, the vicissitudes of the world financial situation, and academic policies. Drawing on hundreds of letters and photos, most of them previously unpublished, the book explores why the Epigraphic Survey chose specific sites for its work, the often grand expectations for its projects and publication program, and the ultimate results. The history of Chicago House, the Survey's headquarters and residence, is described in detail and offers many amusing anecdotes of social life there over the past century. As such, Chicago on the Nile provides a who's who of Egyptologists and archaeologists who worked for and interacted with the Survey to save the endangered texts and reliefs on the ancient monuments of the Nile Valley"--